Characterization of the in vitro core surface proteome of Mycoplasma mycoides subsp. mycoides, the causative agent of contagious bovine pleuropneumonia - Krasteva, I.; Liljander, Anne M.; Fischer, A.; Smith, D.G.E.; Inglis, N.F.; Scacchia, M.; Pini, A.; Jores, Joerg; Sacchini, F. (Elsevier, 2014)
Contagious bovine pleuropneumonia (CBPP), caused by Mycoplasma mycoides subsp. mycoides (Mmm) is a severe cattle disease, present in many countries in sub-Saharan Africa. The development of improved diagnostic tests and vaccines for CBPP control remains a research priority. Polyacrylamide gel electrophoresis and mass spectrometry were used to characterize the Triton X-114 soluble proteome of nine Mmm strains isolated from Europe or Africa. Of a total of 250 proteins detected, 67 were present in all strains investigated. Of these, 44 were predicted to be lipoproteins or cytoplasmic membrane-associated proteins and are thus likely to be members of the core in vitro surface membrane-associated proteome of Mmm. Moreover, the presence of all identified proteins in other ruminant Mycoplasma pathogens were investigated. Two proteins of the core proteome were identified only in other cattle pathogens of the genus Mycoplasma pointing towards a role in host pathogen interactions. The data generated will facilitate the identification and prioritisation of candidate Mycoplasma antigens for improved control measures, as it is likely that surface-exposed membrane proteins will include those that are involved in host-pathogen interactions.